HUBUNGAN PELAKSANAAN PELAYANAN KEFARMASIAN DI APOTEK RSUD LABUANG BAJI MAKASSAR DENGAN TINGKAT KEPUASAAN PASIEN - Mirawati Mirawati; Ermina Pakki; Sany Sahibu (As-Syifaa Jurnal Farmasi, 2011)
This study aims to determine the level of patient satisfaction on the quality of pharmacy service at Labiang Baji hospitals pharmacy Makassar. Has conducted researche about relations implementation of pharmaceutical at the Labuang Baji Baji Hospital Pharmacy Makassar with the level of patient satisfaction.Data from Labuang Baji Hospital Pharmacy from of data about the facility, and drug information service. While filling in the form of the questionnaire. There are 100 respondents who filled in the questionnaire. Respondents were taken using a method accidental. The result showed that existing facilities in inadequate wedge Labuang pharmacies, drug information service has not been fully implemented but the distribution of drug has done well. Meanwhile, from questionnaires completed by patient/families of patients obtained results that the quality of pharmaceutical services in hospital LB was satisfactory, with a value of SME (Society Satisfaction Index ) is 74.70975 to obtain the quality of service B, and categorize the performance of service units in good/satisfactory.Key Word : pharmacy services, respondents, questionnaires